The City School Board of Quezon City a descriptive study - Cardenas, Pedro R. 1920- (s.n.], 1972)
This study was undertaken to find out how the city school board of Quezon City functioned towards the attainment of its objectives. It utilized the descriptive method and documentary analysis. Interviews were used to verify data from documents. It was concluded that the City School Board of Quezon City realized 100 of its objectives within 3 fiscal years from its inception and was higly successful in performing all its duties and functions mandated by law.